2008
DOI: 10.1080/02640410701787791
|View full text |Cite
|
Sign up to set email alerts
|

Arm coordination in elite backstroke swimmers

Abstract: In this study, we assessed arm coordination in the backstroke over increasing speeds by adapting the index of coordination originally used in the front crawl. Fourteen elite male backstroke swimmers swam four trials of 25 m at the speeds corresponding to the 400-m, 200-m, 100-m, and 50-m events. The six phases of the arm stroke were identified by video analysis and then used to calculate the index of coordination, which corresponded to the time between the propulsive phases of the two arms. With increases in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 14 publications
2
35
1
1
Order By: Relevance
“…Further studies should include data about body height and weight, body fat and other 55,56 . Furthermore, data about training strategies to improve swimming techniques 47,48,[57][58][59][60][61] to optimise recovery phases 18,62 and warming-up phases 63,64 which have an effect on swimming performances were not registered. Information about motivation and goal orientation was not recorded.…”
Section: Limitationsmentioning
confidence: 99%
“…Further studies should include data about body height and weight, body fat and other 55,56 . Furthermore, data about training strategies to improve swimming techniques 47,48,[57][58][59][60][61] to optimise recovery phases 18,62 and warming-up phases 63,64 which have an effect on swimming performances were not registered. Information about motivation and goal orientation was not recorded.…”
Section: Limitationsmentioning
confidence: 99%
“…Cappaert et al (1996) found opposing hip/ shoulder rotation in less successful backstroke swimmers, increasing resistive drag. Inefficient utilization of the body roll in intermediate swimmers may affect the positioning of the hand in preparation for the next stroke, which may cause the beginning of the propulsive phase to be lost (Chollet et al, 2008). Hay (1988) stated that this phase of propulsion was effective as the swimmer uses the moving hand in the anteroposterior axis to propel the body forward.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified kinematic differences in stroke mechanics between advanced and intermediate swimmers in all strokes (Cappaert, Pease, & Troup, 1996;Chollet et al, 2008;Leblanc, Seifert, Baudry, & Chollet, 2005;Leblanc, Seifert, & Chollet, 2009;Lerda & Cardelli, 2003;Seifert, Delignieres, Boulesteix, & Chollet, 2007). Although not focusing on shoulder entry angle, Cappaert et al (1995) reported that the hips and shoulders of elite swimmers rotate more symmetrically and with greater amplitude than those of novice swimmers, resulting in differences in body alignment and greater efficiency of propulsion (Kolmogorov, Rumyantseva, Gordon, & Cappaert, 1997).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sin embargo, en la literatura, los datos hallados por García y Veiga (2015) sobre la transición hasta un ciclo de nado podrían aproximarse en parte, ya que también realizaron la fase con empuje al igual que nuestro estudio. Pero la velocidad mostrada por ambos autores en los estilos de crol (1,72 m/s), mariposa (1,68 m/s) y espalda (1,63 m/s) fueron superior a la de otros estudios (Seifert, Chollet y Bardy, 2004;Seifert et al, 2007;Chollet, Carter y Seifert 2006;Chollet, Seifert y Carter, 2008). Además, las diferencias entre las velocidades pudieron estar marcada por el elevado tiempo y la distancia entre el movimiento ondulatorio subacuático y la transición, lo cual redujo la velocidad de espalda, ya que sí la comparamos con la velocidad del nado en superficie (1,24±0,04 m/s), los nadadores del estudio apostaron más por una fase de buceo más larga.…”
Section: La Fase De Transición Al Nado En Superficieunclassified